LEGAL ANALYSIS OF DIVORCE AND DOMESTIC VIOLENCE BASED ON THE LAW ON MARRIAGE AND THE ABOLITION OF DOMESTIC VIOLENCE. - SAADI, MASYHAR (FOCUS: Jurnal of Law, 2023)
The Marriage Law in Indonesia defines marriage as a spiritual and physical bond between a man and a woman as husband and wife to create a harmonious family based on belief in God Almighty. However, not all marriages succeed in achieving this goal and sometimes end in divorce due to various factors, including domestic violence. The research method uses a normative juridical approach in examining divorce due to domestic violence focusing on analyzing library materials and secondary data. This research is descriptive analytical, meaning that it describes and analyzes the applicable positive law and how the law is applied in divorce cases due to domestic violence. This approach examines legislation, legal doctrine, and relevant court decisions. It aims to identify and explain the concept of domestic violence in accordance with the definitions and criteria established by Law Number 1 of 1974 concerning Marriage and Law Number 23 of 2004 concerning the elimination of domestic violence (KDRT). The results of this study are that domestic violence is a valid reason for divorce according to Indonesian law, and religious court judges take it seriously, with suggestions for couples to be wise in dealing with problems and judges to improve their understanding of law and psychology.